PEX1 is essential for glycosome biogenesis and trypanosomatid parasite survival - Mahadevan, Lavanya; Arya, Hemant; Droste, Andrea; Schliebs, Wolfgang; Erdmann, Ralf; Kalel, Vishal C. (Frontiers in Cellular and Infection Microbiology, 2024)
Trypanosomatid parasites are kinetoplastid protists that compartmentalize glycolytic enzymes in unique peroxisome-related organelles called glycosomes. The heterohexameric AAA-ATPase complex of PEX1-PEX6 is anchored to the peroxisomal membrane and functions in the export of matrix protein import receptor PEX5 from the peroxisomal membrane. Defects in PEX1, PEX6 or their membrane anchor causes dysfunction of peroxisomal matrix protein import cycle. In this study, we functionally characterized a putative Trypanosoma PEX1 orthologue by bioinformatic and experimental approaches and show that it is a true PEX1 orthologue. Using yeast two-hybrid analysis, we demonstrate that TbPEX1 can bind to TbPEX6. Endogenously tagged TbPEX1 localizes to glycosomes in the T. brucei parasites. Depletion of PEX1 gene expression by RNA interference causes lethality to the bloodstream form trypanosomes, due to a partial mislocalization of glycosomal enzymes to the cytosol and ATP depletion. TbPEX1 RNAi leads to a selective proteasomal degradation of both matrix protein import receptors TbPEX5 and TbPEX7. Unlike in yeast, PEX1 depletion did not result in an accumulation of ubiquitinated TbPEX5 in trypanosomes. As PEX1 turned out to be essential for trypanosomatid parasites, it could provide a suitable drug target for parasitic diseases. The results also suggest that these parasites possess a highly efficient quality control mechanism that exports the import receptors from glycosomes to the cytosol in the absence of a functional TbPEX1-TbPEX6 complex.